MhYTP1 and MhYTP2 from Apple Confer Tolerance to Multiple Abiotic Stresses in Arabidopsis thaliana - Wang, Na; Guo, Tianli; Wang, Ping; Sun, Xun; Shao, Yun; Jia, Xin; Liang, Bowen; Gong, Xiaoqing; Ma, Fengwang (Frontiers in Plant Science, 2017)
The first YTH domain-containing RNA binding protein (YTP) was found in rat, where it was related to oxidative stress. Unlike characterizations in yeast and animals, functions of plant YTPs are less clear. Malus hupehensis (Pamp.) Rehd. YTP1 and YTP2 (MhYTP1 and MhYTP2) are known to be active in leaf senescence and fruit ripening. However, no research has been published about their roles in stress responses. Here, we investigate the stress-related functions of MhYTP1 and MhYTP2 in Arabidopsis thaliana. Both of the two genes participated in salicylic acid (SA), jasmonic acid (JA), and abscisic acid (ABA) signaling and play roles in plant responses to oxidative stress, chilling, high temperature, high salinity, and mannitol induced physiological drought stress. Moreover, MhYTP1 plays leading roles in SA and ABA signaling, and MhYTP2 plays leading roles in JA signaling and oxidative stress responses. These results will fill a gap in our knowledge about plant YTPs and stress responses and provide a foundation for future attempts to improve stress tolerance in apple.